Microbubble technology for natural rubber latex foam production: The use of various gas-filled microbubbles. Issue 1 (January 2022) - Katkeaw, Kuntida; Khangkhamano, Matthana; Kokoo, Rungrote
In recent years, microbubble technology has attracted great attention in many application fields including water treatment, food processing, oil recovery, surface cleaning, and therapeutic applications. In this paper, microbubbles (MBs) of air, nitrogen, and argon were applied to produce natural rubber latex foams (NRLFs). The bubbles were generated by flowing the gas through a porous diffuser and latex. The effect of gas source on cellular structure, density, elasticity, indentation hardness, and flammability of the bubbled foams was discussed. Argon MBs offered the latex foams with fine cell diameters and uniform cell size distribution resulting in enhanced elasticity and physical properties of the foams. Indentation hardness index and limiting oxygen index value depended significantly on the gas used. By using the microbubble technique, the future prospects in NRLF production can be expected due to its ability in controllable cellular structure.